2019
DOI: 10.1111/iju.14036
|View full text |Cite
|
Sign up to set email alerts
|

Periprostatic nerve block alone versus combined with perineal pudendal nerve block or intrarectal local anesthesia during transrectal ultrasound‐guided prostate biopsy: A prospective randomized controlled trial

Abstract: Objectives To compare the efficacy, safety and cost of combinations of perineal pudendal nerve block + periprostatic nerve block and intrarectal local anesthesia + periprostatic nerve block with the standard technique (periprostatic nerve block). Methods The study was designed as a randomized prospective controlled trial. Patients with elevated serum prostate‐specific antigen values (prostate‐specific antigen ≥4 ng/mL) and/or abnormal digital rectal examination findings were included in the study. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies have pointed out that local anesthetics combined with nerve block can reduce the dosage of opioid analgesics [13]. e results showed that the VAS scores and PONV scores of patients with TAP block decreased evidently at 3 h, 6 h, and 12 h after surgery, and the number of patients who used tramadol for analgesic remedy after surgery was reduced, which greatly improved patient satisfaction.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have pointed out that local anesthetics combined with nerve block can reduce the dosage of opioid analgesics [13]. e results showed that the VAS scores and PONV scores of patients with TAP block decreased evidently at 3 h, 6 h, and 12 h after surgery, and the number of patients who used tramadol for analgesic remedy after surgery was reduced, which greatly improved patient satisfaction.…”
Section: Discussionmentioning
confidence: 84%
“…47 Even PNB may not fully cover the whole duration of postoperative pain, which usually lasts 7 to 10 days after hemorrhoidectomy, but it facilitates same-day patient discharge and assumedly decreases health care costs. 35,39,44,48,49 Complications related to the PNB procedure such as intravenous injection of the anesthetic, permanent nerve lesions, hematoma, abscesses or phlegmons were never reported in our literature search, 14,40,44,50 have been subject to reporting bias. Pudendal nerve block obviously requires adequate training and expertise.…”
Section: Discussionmentioning
confidence: 93%
“…47 Even PNB may not fully cover the whole duration of postoperative pain, which usually lasts 7 to 10 days after hemorrhoidectomy, but it facilitates same-day patient discharge and assumedly decreases health care costs. 35,39,44,48,49…”
Section: Discussionmentioning
confidence: 99%